Tra stereotipo e identità: lo sguardo di Theodor Wonja Michael sulla Germania del Novecento (Altre Modernità, 2022)
The dynamics that rule the coexistence of people and cultural groups show that contemporary society is still bound by the prejudices of the past. Particularly problematic is the gap between those who, born and raised in Europe, are not accepted as part of the community because of their somatic traits that differ from the national model. This issue is analysed from the autobiographical book of Theodor Wonja Michael, a journalist and actor who lived under a spirit of resilience. His body, made vulnerable by the colour of his skin and by his Cameroonian heritage, could react on each occasion to the rejection of a Germany which, for years, demanded to speak in his place, forcing him to appear as a savage in the famous human zoos (Völkerschauen), in spite of his strong feeling of belonging to Germany. The historical events lead us to reflect on the principles governing the construction of the stereotypical image of ‘us’ and ‘the other’ and on the practical tools used to support these ideas. Deutsch sein und schwarz dazu (2015) tells the story of a man and, at the same time, of a group of individuals defrauded of their identities in order to embody the prejudices of the times.
Keywords: Post-colonialism; human zoos (Völkerschauen); identity; Theodor W. Michael